Education for All : Compensating for Disadvantage in Mexico - Patrinos, Harry Anthony; Shapiro, Joseph; Trevino Moreno, Jorge (World Bank, Washington, DC, 2012)
Education for all means learning for all. It means closing the advantage gap-making sure that the children of the poor and disadvantaged achieve the same levels of learning as all other children. This is one of the great challenges any country can face. It is a particular challenge in a diverse country such as Mexico, where many children do not speak Spanish, live in villages inaccessible by roads and cannot afford such basic expenditures as school uniforms.